A novel approach to fabricate zeolite membranes for pervaporation processes. Issue 18 (14th May 2015) - Alomair, Abdulaziz A.; Al-Jubouri, Sama M.; Holmes, Stuart M.
<x xml:space="preserve">Abstract</x> A method has been demonstrated to synthesise effective zeolite membranes from existing crystals without a hydrothermal synthesis step.